2003
DOI: 10.1152/jn.00195.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Natural Scenes in Cat V1

Abstract: Studies on processing in primary visual areas often use artificial stimuli such as bars or gratings. As a result, little is known about the properties of activity patterns for the natural stimuli processed by the visual system on a daily basis. Furthermore, in the cat, a well-studied model system for visual processing, most results are obtained from anesthetized subjects and little is known about neuronal activations in the alert animal. Addressing these issues, we measure local field potentials (lfp) and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 45 publications
9
123
2
Order By: Relevance
“…Indeed, a number of recent studies have shown that, when given appropriate stimuli, neurons that previously showed high response variability can exhibit highly reproducible responses (Mainen and Sejnowski, 1995;Bair and Koch, 1996;de Ruyter van Steveninck et al, 1997;Buracas et al, 1998;DeWeese et al, 2003;Gur and Snodderly, 2006) (but see Kayser et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of recent studies have shown that, when given appropriate stimuli, neurons that previously showed high response variability can exhibit highly reproducible responses (Mainen and Sejnowski, 1995;Bair and Koch, 1996;de Ruyter van Steveninck et al, 1997;Buracas et al, 1998;DeWeese et al, 2003;Gur and Snodderly, 2006) (but see Kayser et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that synchronization between sets of neurons might be used to indicate that the features represented by the different neurons should be grouped or bound together, thus facilitating segmentation of simultaneously present objects from each other and from the background. The hypothesis is that stimulus-dependent neuronal synchronization (SDS) would be useful, in that particular sets of features might need to be bound together for one object, but not for another object (Kayser et al 2003;Malsburg 1990;Singer 1999;Singer and Gray 1995). We specifically address this hypothesis, and more generally, the relative quantitative contributions of SDS and firing rates to information encoding, by analyzing the responses of inferior temporal cortex neurons, where neurons respond to objects and faces (Desimone et al 1984;Gross et al 1972;Perrett et al 1982Perrett et al , 1992Rolls and Deco 2002;Rolls et al 1994;Tanaka 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoencephalography MEG was used in the same participants to measure stimulus-induced sustained gamma oscillations in response to the presentation of a high-contrast, static, 3 cycle/degree grating patch. Similar low-level visual stimuli have previously been shown to be a strong inducer of gamma oscillations in the primary visual cortex of cats (15,16) and humans (17)(18)(19). In subsequent recording sessions with the same participants, fMRI was used to measure the BOLD response in primary visual cortex to the identical visual stimulus used in the MEG.…”
mentioning
confidence: 99%